A 1H NMR-based metabolomic approach to study the production of antimalarial compounds from Psiadia arguta leaves (pers.) voigt. (August 2020) - Mahadeo, Keshika; Grondin, Isabelle; Herbette, Gaëtan; Palama, Tony L.; Bouchemal, Nadia; Soulange, Joyce; Laulloo, Sabina Jhaumeer; Sadeyen, Joelle; Humeau, Laurence; Frederich, Michel; Gauvin-Bialecki, Anne; Kodja, Hippolyte
Abstract: Psiadia arguta (Asteraceae) is endemic to the island of Mauritius in the Indian Ocean. The species is traditionally used to treat various ailments, such as its use as an expectorant or for the treatment of bronchitis and asthma. Preliminary biological screenings have displayed the antimalarial ( Plasmodium falciparum ) and anticancer (HeLa human cell line) potential of P. arguta leaves . The phytochemical investigation of this plant has led to the isolation and characterization of sixteen compounds including five antiplasmodial molecules. The accumulation of the antiplasmodial compounds during the growth of the plant was studied by a 1 H NMR-based metabolomic approach. In order to identify factors influencing the production of bioactive compounds, young plants of P. arguta were multiplied using in vitro culture techniques, and micro-propagated plants at different stages of development were acclimatized and followed for the experiments. The multivariate data analysis showed an accumulation of four bioactive compounds in the leaves of P. arguta when these plants were challenged with a biotic stress: labdan-13( E )-en-8α-ol-15-yl acetate, labdan-8α-ol-15-yl acetate, labdan-13( E )-ene-8α-ol-15-diol, and (8 R, 13 S )-labdan-8, 15-diol. Graphical abstract: Image 1 Highlights: In vitro Psiadia arguta was explored for production of antiplasmodial compounds. The influence of environmental factors throught the growth of Psiadia arguta was studied by NMR metabolomic. The production of antiplasmodial compounds was related to biotic stresses. The characterization of bioactive compounds was performed using 1D and 2D NMR.